Inhibisi Prostitusi: Kajian Dampak Kebijakan Penutupan Lokalisasi Teleju oleh Pemerintah Kota Pekanbaru - M. Zainuddin (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This research to analyze the impact of closure policy Teleju brothel by Pekanbaru goverment in 2010. Guidelines for works are Pekanbaru Local Regulations No. 12 of 2008 on Social Orderliness. Closure this brothel inflicts positive and negative impact for society.The research was conducted to obtain early stage formula for the government to take action against the prostitution activities. This research uses policy research approach with a qualitative method, because in prostitution activities and prohibition by goverment is an assessment that needs to be done by analyzing documents and unstructured interview. The results showed that after the closing of the Teleju brothel have an impact on the deployment of a prostitution and affect the economy of the surrounding residents. Government seeks to tackle prostitution in Pekanbaru by moving the brothel, conduct regular raids and provide training. The effort is considered to be less than the maximum because the handling is not based on the root of the problem and not programmed properly. There are several causes of failure of government to overcome the prostitution problem in Pekanbaru, including: policy content is less focus on the prostitution problem, the government did not proceeds with data, lack of financial support, contra productive programs between local government with the police and TNI, and the policy object is difficult to be given understanding.